Nonlinear Doppler reflectometry power response. Analytical predictions and full-wave modelling. (28th February 2019) - Krutkin, O L; Gusakov, E Z; Heuraux, S; Lechte, C
Abstract: The transition of Doppler reflectometry diagnostics to nonlinear regime of scattering is studied analytically with the use of the perturbation theory applied to the Helmholtz equation. Density fluctuations with large radial correlation length, O-polarisation of the probing beam, linear background density profiles and slab geometry are considered. Formulae for onset of nonlinearity are derived for different parameter ranges. Obtained results are generalised for the arbitrary turbulence radial correlation length. The results of the physical optics model are reproduced in one particular case, while new formulae is obtained for different parameter ranges and their experimental relevance is demonstrated. A qualitative explanation for scattered signal nonlinear power dependence is proposed. Analytical results are validated with IPF-FD3D code full-wave numerical modelling for radially uniform and fully 2D turbulence.